Presymptomatic testing for autosomal dominant spinocerebellar ataxia type 1. Issue 7 (July 1993) - Shrimpton, A E; Davidson, R; MacDonald, N; Brock, D J
Abstract : Presymptomatic testing was done on four people from a large family in which an autosomal dominant form of spinocerebellar ataxia was segregating. Earlier genetic analysis had shown that in this family the disorder was tightly linked to an informative microsatellite polymorphism on chromosome 6p. Two subjects with prior risks of 50% of developing the disease had final risks after testing of 2%; the other two with prior risks of 25% had final risks of 1%. Chromosome 6p linked spinocerebellar ataxia may now be added to Huntington's disease as a late onset disorder in which genetic linkage may be used to carry out presymptomatic testing.